The pelvic and hindlimb myology of the basal titanosaur Epachthosaurus sciuttoi (Sauropoda: Titanosauria) - Ibiricu, Lucio Manuel (2018)
Epachthosaurus sciuttoi is a basal titanosaur from the early Late Cretaceous of central Patagonia, Argentina. Here, we present the reconstruction of the pelvic and hindlimb musculature of this titanosaur, based on the soft tissue data of extant archosaurs. The majority of the pelvic, hindlimb and pes muscles are within a decisive and positive level of inference. Comparison with a derived titanosaur such as Neuquensaurus, shows several morphological differences which are directly related with the muscular attachments, supporting differences about the musculature arrangement between these two sauropod dinosaurs. For example, the anterior projection of the preacetabular process of Neuquensaurus extends more laterally, whereas in Epachthosaurus the preacetabular process is laterally less extended. The fibular lateral tuberosity in Neuquensaurus is closer to the fibular head than it is in Epachthosaurus. The femoral fourth trochanter in Neuquensaurus is closer to the femoral head than it is in Epachthosaurus. Likewise, the caudofemoralis longus may have extended more distally in the tail in Epachthosaurus.These differences, among others, may have influenced the muscular arrangement and, therefore, the locomotor function abilities of these titanosaurs. Finally, this myological description of Epachthosaurus, where twenty one muscles were reconstructed, constitutes useful data for researches interested in functional anatomy.